2010
DOI: 10.1007/s00432-009-0754-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of microRNA-related gene polymorphisms on survival of patients with colorectal cancer

Abstract: None of the 40 miRNA-related gene polymorphisms investigated in this study was found to be an independent prognostic marker for Korean patients with surgically resected colorectal cancer. However, further studies are warranted to clarify the role of miRNA-related gene polymorphisms as a prognostic biomarker for colorectal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 15 publications
2
41
1
Order By: Relevance
“…Furthermore, other epidemiological studies have reported the association of the C allele with increased risk of congenital heart disease (26), hepatocellular carcinoma (27) and gastric cancer (28). To our knowledge, there have been only two studies that have investigated the prognostic impact of the hsa-mir-196a2 polymorphism in colorectal cancer (14,16). Consistent with our result, these studies also failed to identify any significance of the hsa-mir-196a2 C polymorphism as a prognostic biomarker.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, other epidemiological studies have reported the association of the C allele with increased risk of congenital heart disease (26), hepatocellular carcinoma (27) and gastric cancer (28). To our knowledge, there have been only two studies that have investigated the prognostic impact of the hsa-mir-196a2 polymorphism in colorectal cancer (14,16). Consistent with our result, these studies also failed to identify any significance of the hsa-mir-196a2 C polymorphism as a prognostic biomarker.…”
Section: Discussionsupporting
confidence: 82%
“…However, there were few associations identified for SNPs in pre-miRNA with prognostic significance in colorectal cancer patients (14)(15)(16). In the present study, we investigated whether polymorphisms in pre-miRNA genes influence the outcome of patients with surgically resected colorectal cancer.…”
Section: Introductionmentioning
confidence: 93%
“…Hence, there is a need for studies for evaluating the role of various miRNAs in progression of the GERD>BE>EAC pathway. Recently, it has been shown that genetic polymorphisms in miRNA encoding genes and miRNA binding sites (3′ UTR of genes) may have a role in the disease [55][56][57][58][59].…”
Section: Mirnas In Be and Eacmentioning
confidence: 99%
“…Genetic variants in miRNA biogenesis pathway genes have been shown to be associated with the risk of several cancers or related diseases such as bladder cancer [13], esophageal cancer [14], renal cell carcinoma [15], prostate cancer [16], and premalignant oral lesions [17] and the prognosis of colorectal cancer [18], and renal cell carcinoma [18,19]. However, as yet, no study has shown the association between the polymorphisms in the miRNA biogenesis pathway genes and the risk of breast cancer.…”
Section: Introductionmentioning
confidence: 96%